Natural regeneration potential of the soil seed bank of different land use types in swamp forest of Ogun river watershed, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
Unsustainable land uses are a major indicator of human activities that contribute to land degradation, a menace that inhibits the regeneration of forest estates. This study, therefore, investigated the effects of land use practices on regeneration potentials of the Swamp Forest of the Ogun River Watershed (ORW) with a view to providing baseline information towards sustainable watershed management. The swamp forest of ORW was stratified into Natural Forest (NF), Disturbed Forest (DF), and Farm Land (FL) for natural regeneration assessment of the soil seed bank. Two systematic line transects of 1000 m length were used in the laying of the sample plots. Sample plots of 25 m x 25 m were established in alternate positions along the transects. Ten plots in each land use type were randomly selected for soil core sample collection. The soil samples were placed in individual 20 cm × 30 cm × 1 cm containers in a screen house. The trays were watered regularly to induce germination, and seedlings were checked for emergence fortnightly for 18 months. Descriptive statistics were used to analyze the data. A total of 1,121 seedlings distributed among 26 families emerged from the soil of various land use types. The FL had the highest number of germinated seeds (544±42.9 seedlings), which were mostly invasive herbaceous plants, followed by DF (378±39.22 seedlings) with similar invasive species. The NF with 199±28.41 seedlings had more tree species, similar to the aboveground tree species of the study area. More invasive herbaceous plants dominated FL and DF compared to NF, which had more tree seedlings from the seed bank in relation to aboveground tree species.
Keywords: Degradation; Persistent seeds; Regeneration; Soil seed bank